Evolução e presente status do cenário inflacionário da cosmologia - Ferreira, Paulo André Vasconcelos (2020)
The first inflationary scenario proposed in 1981 by the North American physicist Alan Guth solves the flatness problem and the horizon problem for which the standard cosmological model has no answer. However, Guth himself identified problems when trying to implement it. Other models were proposed by Andrei Linde, Andreas Albreacht and Paul Steinhardt in order to solve the flaws of the original scenario. Despite this, these models are also limited. The purpose of this work is to discuss the limitations and present status of different inflationary models in applications to cosmology.